Effect of Different Doses of Vermicompost and Inorganic Fertilizer on Growth and Yield of Radish (Raphanus sativus) Varieties in Kaski, Nepal - Marahatta, Sunira (International Journal of Applied Sciences and Biotechnology, 2025)
The research was conducted at Kaski, Nepal from March to June 2021 to study different doses of vermicompost and inorganic fertilizers on growth and yield of radish (Raphanus sativus) The experiment was laid out in a two-factor Randomized Complete Block Design (RCBD) with 12 treatments and 3 replications. The first factor was variety—Tokinashi and Mino Early—and the second factor was fertilizer level, consisting of six treatments: control (no fertilizer), 75% vermicompost + 25% inorganic fertilizer, 50% vermicompost + 50% inorganic fertilizer, 25% vermicompost + 75% inorganic fertilizer, 100% inorganic fertilizer, and 100% vermicompost. Vegetative parameters were recorded at 20, 30, 40 and 50 days after sowing whereas yield parameters: biological yield per plant, economic yield per plant, root length and root diameter were recorded at 55 days after sowing. It has been observed that the growth and yield attributing characters of radish were significantly affected by variety and fertilizer levels. Mino early recorded highest result for all vegetative parameters. However, highest yield attributing characters was recorded from Tokinashi. The combination of inorganic fertilizer with 50-75% with vermicompost gave better result in terms of both growth and yield attributing parameters than 100% inorganic fertilizer alone. Interaction effect of variety and fertilizer levels for all parameters at all dates of observations was found to be non-significant. Overall, the highest yielded was from variety, Tokinashi (4.55kg/m2) and the fertilizer combination of 50% vermicompost + 50% inorganic fertilizer (5.61kg/m2). Therefore, this combination is recommended for late-season radish production in Kaski, Nepal. Int. J. Appl. Sci. Biotechnol. Vol 13(4): 153-161.